Upaya Guru Pendidikan Agama Islam dalam Menanamkan Nilai-nilai Moderasi Beragama bagi Siswa di SMP Negeri 01 Mandiraja Banjarnegara - Lu’luAyunah, Khudaefah; Ariyani , Dewi (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
This research aims to examine the efforts of Islamic Religious Education (PAI) teachers in instilling values of religious moderation at SMP Negeri 01 Mandiraja. Using a descriptive qualitative approach, the study involves observations, interviews, and documentation from PAI teachers, eighth-grade students, and the school principal. The findings indicate that PAI teachers employ various effective strategies, such as integrating moderation values into the curriculum through exemplary stories and everyday life examples, aimed at teaching students to appreciate differences and adopt a tolerant attitude. Additionally, the practice of greetings, smiles, and salutations (3S), along with group discussions, contributes to positive interactions among students. Activities such as Quran recitation, literacy, and Dhuha prayers strengthen students' spiritual character and instill important values of moderation. The management of an inclusive school environment and religious events that respect differences further reinforce the school's commitment to religious tolerance. Through process-based evaluations, teachers can assess students' understanding of moderation values in their social interactions. The academic contribution of this research is expected to serve as a reference for the development of better curricula and educational practices in other schools, as well as to encourage further research on the effectiveness of the methods used in a broader context